ANALISIS NILAI MORAL NOVEL SI ANAK BADAI KARYA TERE LIYE DAN PEMANFAATANNYA SEBAGAI BAHAN AJAR PENGUATAN PROYEK PROFIL PELAJAR PANCASILA - Pradana, Muhammad; Kusmayanti, Desti; Maulana, Irpan (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study looks at the ethical principles embedded in Tere Liye's novel Si Anak Badai, along with its application as a digital educational resource (e-book) within the Pancasila Student Profile Strengthening Project (P5). This study employs a descriptive qualitative approach through content examination, including reading, listening, and taking notes to examine the text, quotes, dialogues, and stories in the book. The data included 90 quotes that show moral values, grouped into four areas: relationships with yourself, other people, the environment, and God. The results showed that 41 of these quotes connected directly to the six parts of P5: belief in and devotion to the Almighty, valuing global variety, collaborative spirit, independence, analytical reasoning, and innovative thinking. The digital teaching material was tested on 29 students at SMAN 1 Cipeundeuy and got positive feedback, with most of the responses being "good" or "very good." These findings show that the moral values in “Si Anak Badai” are suitable to be used in literature lessons to help build students' character based on Pancasila values.